DESAIN PEMBELAJARAN BANGUN DATAR PADA KELAS I BERKONTEKS MAKANAN TRADISIONAL INDONESIA BERBANTUAN MEDIA SMART SPINNER MELALUI PENDEKATAN PMRI - Setya Wardani, Anna; Farida Nursyahidah; Partiyah; Rasiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Shapes is one of the materials that is considered difficult in learning geometry. Students have difficulty understanding the basic concepts of flat shapes in distinguishing quadrilaterals, triangles and circles. Therefore, it is necessary to organize learning activities that emphasize understanding basic concepts using appropriate media and approaches. The aim of the research is to design a learning trajectory that helps students understand the basic concepts of flat shapes in differentiating rectangular, triangular and circular shapes by utilizing the context of traditional Indonesian food with the help of Smart Spinner media. The research method used by design research consists of three stages, preliminary design, pilot experiment, and retrospective analysis. The learning approach used was PMRI with the research subjects being 6 students at SDN Palebon 03 Semarang. Data collection was carried out through observation, interviews, photos and field notes. The learning track consists of 3 activities, namely recognizing flat shapes in the context of traditional Indonesian food through Smart Spinner media, identifying shapes of flat shapes, and solving contextual problems related to flat shapes. The results of the research show that the learning trajectory obtained is able to help students understand the basic concepts of flat shapes in distinguishing rectangular, triangular and circular shapes more easily and meaningfully.